Pengaruh Quality Of Work Life Dan Locus Of Control Internal Terhadap Bank Kaltim Samarinda - Rahayu Nova Daryati; Yana Ulfah; Robiansyah Robiansyah (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the influence of Quality of Work Life and Locus Of Control on Employee Performance KALTIM Bank Main Branch Samarinda. Basic theory used human resource management by using multiple linear regression analysis with 45 samples. The conclusion of this study: Partially Showed independent variables Quality of Work Life (QWL) has a value of t is greater than t table and its significance is smaller than Î± 0.05, this means partial independent variable Quality of Work Life (QWL) significantly affects the performance of Bank Employees KALTIM Main Branch Samarinda Partially showed independent variables Locus Of Control has the value t is greater than t table and its significance is smaller than Î± 0.05 this means partial Locus Of Control variables significantly influence employee performance KALTIM Bank Main Branch SamarindaKeywors : Quality of Work Life, Locus of Control - Performance